TINDAK UJAR KOMISIF PADA IKLAN BERBAHASA INGGRIS DALAM MAJALAH COLOURS (SUATU KAJIAN PRAGMATIK) - Sengke, Fransine (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is focused on the commissive act in Colours Garuda Indonesia Magazines. The commissive act is one of many illocutionary acts which essentially involves the speaker committing himself to behave in some required ways, for instance promising and swearing. The aim of this research is to find out and to analyze the categories of commissive in Colours Garuda Indonesia Magazines advertisement especially Consumer Advertisement that refer to illocutionary function and to analyze how they are performed. In collecting the data, the writer focused on Colours Garuda Indonesia Magazines, editions January 2015, February 2015 and March 2015. Then the writer analyzes the collected data descriptively by using the theory of Austin and Tallei. The result of this study shows that there is a linguistics message in every text of an advertisement; it is used in the advertisement to give information and emotional response. There is commissive function of offering in every utterance in advertisement and the other commissive function such as persuading and promising which are found in consumer’s advertisements. It is expected that this study may help the students or readers to comprehend the illocutionary act, particularly about the commissive in the consumer advertisement in Colours Garuda Indonesia Magazines.